Nitric oxide contributes to protein homeostasis by S-nitrosylations of the chaperone HSPA8 and the ubiquitin ligase UBE2D - Valek, Lucie (Redox Biol, 2018)
Upregulations of neuronal nitric oxide synthase (nNOS) in the rodent brain have been associated with neuronal aging. To address underlying mechanisms we generated SH-SY5Y neuronal cells constitutively expressing nNOS at a level similar to mouse brain (nNOS+ versus MOCK). Initial experiments revealed S-nitrosylations (SNO) of key players of protein homeostasis: heat shock cognate HSC70/HSPA8 within its nucleotide-binding site, and UBE2D ubiquitin conjugating enzymes at the catalytic site cysteine. HSPA8 is involved in protein folding, organelle import/export and chaperone-mediated LAMP2a-dependent autophagy (CMA). A set of deep redox and full proteome analyses, plus analysis of autophagy, CMA and ubiquitination with rapamycin and starvation as stimuli confirmed the initial observations and revealed a substantial increase of SNO modifications in nNOS+ cells, in particular targeting protein networks involved in protein catabolism, ubiquitination, carbohydrate metabolism and cell cycle control. Importantly, NO-independent reversible oxidations similarly occurred in both cell lines. Functionally, nNOS caused an accumulation of proteins, including CMA substrates and loss of LAMP2a. UBE2D activity and proteasome activity were impaired, resulting in dysregulations of cell cycle checkpoint proteins. The observed changes of protein degradation pathways caused an expansion of the cytoplasm, large lysosomes, slowing of the cell cycle and suppression of proliferation suggesting a switch of the phenotype towards aging, supported by downregulations of neuronal progenitor markers but increase of senescence-associated proteins. Hence, upregulation of nNOS in neuronal cells imposes aging by SNOing of key players of ubiquitination, chaperones and of substrate proteins leading to interference with crucial steps of protein homeostasis.